Interpretation of loga statues in Bada Valley culture: an interpretive anthropology study - Yudhanto, Sigied Himawan; Prayoga, Dedy Eka Timbul (Pascasarjana Institut Seni Indonesia Surakarta, 2025)
This study analyzes the symbolic meaning of Loga statues in the Bada Valley through the interpretive, symbolic anthropology approach of Clifford Geertz and the symbolic interpretation of Victor Turner. Using Geertz's theory, the perspective views Loga statues as cultural